Iron Age hillfort defences and the tactics of sling warfare - Robertson, Peter (Writer on experimental archaeology) (Archaeopress, 2016)
Sling accuracy at a hillfort is measured here for the first time, in a controlled experiment comparing attack and defence across single and developed ramparts